Google Classroom-Assisted Mobile in Language Learning for Students of Primary School Teacher Education - Muhamad Sofian Hadi; Lidiyatul Izzah; Aliya Nafisa Karyadi (English Language in Focus (ELIF), 2021)
Language learning activities are required for all students of the Faculty of Education at Universitas Muhammadiyah Jakarta. So far, the learning process in the classroom has been carried out conventionally. Lecturers come to class, deliver lessons, and assign homework to students. Teaching and learning activities are routine activities that frequently bore students and make them uninterested in taking the class. Students' boredom requires an alternative learning process that does not adhere to conventional concepts but has adopted novelty by using free applications that can be downloaded on each student's smartphone. Google Classroom, an online learning system that allows lecturers and students to carry out the learning process wherever and whenever they want, is one solution that can be provided. It is expected that students' English learning will improve as a result of their use of Google Classroom. As a result, it offers a variety of new learning opportunities and can accommodate students' preferences. The use of Google Classrooms is also consistent with the rapid development of technology, which is supported by the slogan of the Industrial Revolution era 4.0. It has also touched the 5.0 era, which leads to the use of technology products that can be used in the classroom learning process and supports the new minister of education's policies regarding freedom of learning.